DEER ON AIRPORTS: AN ACCIDENT WAITING TO HAPPEN - Wright, Sandra E.; Dolbeer, Richard A.; Montoney, Andrew J. (DigitalCommons@University of Nebraska - Lincoln, 1998)
The authors analyzed data on civil aircraft strikes with wild ungulates (deer [Odocoileus spp.], elk [Cervus canadensis] and moose [Alces alces]) in the U.S. from the Federal Aviation Administration (FAA) Wildlife Strike Database and the National Transportation Safety Board (NTSB) Aviation Accident Database for 1983 to 1997. Prior to 1991, the FAA Form 5200-7 for reporting strikes was designated solely for bird strike data, thus, strike reports for non-avian species prior to 1991 are underrepresented. A total of 343 ungulate strikes was reported, 48 from 1983 to 1990 and 295 from 1991 to 1997. Forty-four states reported ungulate strikes with 77% of the reports from states east of the Mississippi River. November had more (P < 0.01) strikes (23 %) than any other month. The strike rate (number/hr) was four to nine times greater (P < 0.01) at dusk than at night or dawn. Almost two-thirds of strikes (P < 0.01) occurred during landing, making landing at dusk in November the most likely time for deer strikes. About 79% of strikes had an effect on flight. Aircraft were damaged in 83% of strikes. Only 14% of reports indicating damage provided estimates of cost of repairs. The mean cost for these reports was $74,537. Reported human injuries have been few, but the potential exists for a major disaster. Aircraft with capacity of 101 to 380 passengers were involved in 45 (14%) of the reported strikes. Airports should adopt a "zero tolerance" for deer within the operations area. Deer removal by professional shooters, in conjunction with permanent exclusion with 3 m high fencing, is the preferred management action.